The effect of phase-shifting transformer angle value on system congestion and determination of ideal phase angle - Aydin, Faruk; Yigit, Kenan; Acarkan, Bora (SPRINGER, 2025)
The phase-shifting transformer (PST) is a special type of transformer that controls the active power flow in the network and ensures that the transmission lines are loaded at the desired level. In this study, the effect of phase angle value, which is an important parameter in PST, on system limitations, is examined. For this purpose, an IEEE 39-bus test system was modeled for different scenarios. In the simulation studies, not only overloaded lines but also lines approaching their thermal limits were taken into account by using the power system visualization features of the PowerWorld program. Thus, it was tried to determine the ideal phase angle value for the power system in the current scenario. As a result, it has been seen that the PST operated at the ideal angle has the features of controlling the power flow and reducing congestion. However, incorrect phase angle regulation may cause overload on the entire grid. Therefore, it is emphasized that the power system should be evaluated as a whole while calculating the angle value of the PST. In this paper, unlike conventional studies, the ideal phase angle that will reduce the installation cost has been determined, taking into account lines with overloading risks. A wide range of tests at different angle values and the IEEE 39-bus test system demonstrate the effectiveness of the proposed methodology. Additionally, the interaction between PSTs in the same network, combination of PST with energy storage systems and possible network topology changes in congestion management were also examined.
Keywords: Phase-shifting transformer; Power flow analysis; Transmission system congestion; Phase shift angle; Power flow control; FACTS; POWER-FLOW CONTROL; TRANSMISSION-LINES; ADJUSTMENT; Engineering